The Political Economy of a Northern Ireland Border Poll - Seamus McGuinness; Adele Bergin (Institute of Labor Economics (IZA), 2019)
Given the increased prominence of a border poll in Ireland, particularly following the outcome of the Brexit referendum, this paper provides an initial assessment of some of the issues that are likely to become central in any debate on this issue. We examine the relative income and growth position of Northern Ireland within a UK and Irish regional framework over time. We further compare, and contrast, in detail aspects of the structure of both economies on the island of Ireland in the areas of educational attainment, trade orientation and the role of FDI. The paper goes on to analyse other relevant issues, such as the relative strength and weaknesses of the healthcare systems and the factors determining the potential economic cost of Irish unification. The objective of the research is to initiate an evidence-based approach to the question of a border poll and to provide an initial indication of the breadth of detail and analysis required for any debate to proceed in a meaningful manner.
Keywords: P52; J01; J10; R10; 330; border poll; Brexit; Northern Ireland